RUSYA'DA KÜRDOLOJİ'NİN GELİŞİMİ - Çağlayan, Erhan (My University, 2015)
XIX. yüzyılda Rusya'da Kürtçenin öğrenilmesiyle birlikte Kürtçe eserlerin çevirisine başlanır. Bu dönemde Rusya'da "Kürdoloji" isimli bilim alanı ortaya çıkar, Sovyetler döneminde ise Kürtlerin tarih, edebiyat ve kültürü daha kapsamlı şekilde araştırılır. 1950'li yıllardan itibaren SSCB'de bu alanda çok sayıda önemli araştırmalar yapılır. Rusya Bilimler Akademisi Şarkiyat Enstitüsü Petersburg (Leningrad) şubesinde "Kürt Kurulu" oluşturulur, daha sonra bu kurul, Kürdologlar Grubu'na dönüşür. SSCB'de Kürtlerin tarihi; özellikle yeni dönemde Türkiye, Irak ve İran Kürtlerinin siyasi ve sosyal tarihi geniş bir şekilde araştırılır. Bu araştırmalar, özellikle de Kürt halkının milli mücadele tarihiyle ilgili eserleri, Sovyet Kürdolojisi'ni önemli ölçüde zenginleştirir. Günümüz Rusya'sında Kürt tarihiyle ilgili araştırmalar devam etmektedir. Bugün Kürt ve Kürdistan araştırmaları alanında Rusya'da iki ana merkez faaliyette bulunmaktadır: Rusya Bilimler Akademisi Şarkiyat Enstitüsü'nde faaliyette bulunan Kürdologlar Grubu ve 1994 yılında tesis edilen Kürt Araştırmaları Merkezi.

The study of the Kurdish language and translation of works from the Kurdish language began in the nineteenth century. In that period, the term -Kurdology- appeared in academic literature in Russia. During the Soviet period, the history, literature and culture of the Kurds were more deeply investigated. From the 1950s onward, a large number of important studies in this field were carried out in the USSR. A-Kurdish Cabinet- was formed and organized in St. Petersburg (Leningrad) which bore the title -The Department of Oriental Studies of the Russian Academy of Sciences.- It later became known as the Kurdologists' Group. In the USSR, history of the Kurds was widely studied, especially including the new era and the political and social history of Turkey, Iraq and Iran. Research works on the history of the national struggle of the Kurdish people significantly enriched the Soviet Kurdology. A considerable amount of research and survey work on the history of Kurdish people are still performed in Russia today. Two major centers are operating in Russia in the field of Kurdish Studies: the Kurdologists' Group at the Institute of Oriental Studies of the Academy of Sciences of Russia and the Kurdish Studies Center founded in 1994.
THE DEVELOPMENT OF KURDOLOGY IN RUSSIA